First drop of crimson - Frost, Jeaniene (Frost, Jeaniene. Night Huntress novel., 2010)
When a demon shape-shifter begins stalking an innocent mortal, Spade, a powerful vampire, is duty-bound to protect this woman who arouses his deepest hungers, even if it means destroying his own kind.